Fake News: Where Journalists and Audiences Meet (and Where They Don’t) - Carazo-Barrantes, Carolina (2023)
This article gives voice to two protagonists of the disinformation phenomenon: audiences and journalists. A two-objective comparative analysis is presented: on the one hand, to explore the audiences’ role in stimulating the disinformation phenomenon in Costa Rica and characterize the reception dynamics and interaction that they establish with fake news within the country; on the other hand, to give journalists a voice to compare and contrast their perceptions with their audiences’ perceptions. A qualitative methodology based on semi-structured interviews with a small and non-representative sample of Costa Rican journalists holding leadership positions at some of the country’s most important media outlets was used. Also, six discussion groups with audiences were held. This article performs a comparative analysis of what journalists and participating audiences think about the disinformation phenomenon, the term “fake news,” the responsibilities in the fight against this problem and the possible solutions. The results suggest that, according to journalists, misinformative content circulates on social media and does not come from the traditional media they represent. In contrast, audiences present an antagonistic position since they tend to associate disinformation with the traditional media. However, they also consider traditional media as a source of verification of false content circulating on social media.